Pembinaan Karakter Tanggung Jawab Santri Melalui Kegiatan Ekstrakulikuler Tahfizul Quran Di Pondok Pesantren Daarul Istiqlal Medan Kecamatan Patumbak Kabupaten Deli Serdang - Najihani; Soiman; Khairuddin (Philosophiamundi, 2024)
This research is motivated by the Tahfizul Quran extracurricular activities, which aim to build the character of responsibility among students at Pondok Pesantren Daarul Istiqlal Medan, Patumbak District, Deli Serdang Regency. This research uses a descriptive qualitative method. It provides descriptive data in the form of transcripts, interviews, field notes, personal documents, memos, and other documents. The data collection techniques include observation, interviews, and documentation. The data analysis techniques involve data reduction, data presentation, and data verification. The research results reveal that the character-building of responsibility among students through the Tahfizul Quran extracurricular activities at Pondok Pesantren Modern Daarul Istiqlal has been carried out by the supervising teachers. The students' sense of responsibility is instilled through the Tahfizul Quran extracurricular activities. The programs implemented aim to foster students' responsibility through these activities. However, the challenges faced by the supervising teachers in achieving the targets include the frequent holidays experienced by students, which can cause them to forget their memorization.